2008
DOI: 10.4103/0250-474x.44602
|View full text |Cite
|
Sign up to set email alerts
|

Formulation development and release studies of indomethacin suppositories

Abstract: Indomethacin suppositories were prepared by using water-soluble and oil soluble suppository bases, and evaluated for in vitro release by USP I and modified continuous flow through bead bed apparatus. Effect of the Tween 80 (1% and 5%) was further studied on in vitro release of the medicament. Release rate was good in water-soluble suppositories bases in comparison to oil soluble suppositories bases. Release was found to be greater in modified continuous flow through bead bed apparatus. When surfactant was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Thus, lower‐average molecular weight PEGs as PEG 400 are sometimes incorporated into suppositories in proportions of 30%–70%. PEG 1000 can be used in proportions of 40%–75% . In a recent study, PEG adducts between cetirizine or indomethacin and PEG 400 were observed after 5 days of incubation at 80°C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, lower‐average molecular weight PEGs as PEG 400 are sometimes incorporated into suppositories in proportions of 30%–70%. PEG 1000 can be used in proportions of 40%–75% . In a recent study, PEG adducts between cetirizine or indomethacin and PEG 400 were observed after 5 days of incubation at 80°C .…”
Section: Introductionmentioning
confidence: 99%
“…PEG 1000 can be used in proportions of 40%-75%. 17 In a recent study, PEG adducts between cetirizine or indomethacin and PEG 400 were observed after 5 days of incubation at 80 • C. 14 The PEG adducts were separated and identified using supercritical fluid chromatography (SFC) hyphenated to mass spectrometry (MS). A few studies exist, where the kinetics of esterification with ethylene glycol has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine the pharmaceutical availability of the drug in vitro studies, the amount of the drug substance released from the dosage form and dissolved in the surrounding liquid as well as the rate at which this process occurs should be determined [28]. The quantity of a drug released from suppositories depends on many factors such as drug solubility in the base, addition of surfactants and solubility of a drug in a dissolution medium [1,12,30]. The type and quantity of a surfactant included in the suppository base cause the increase or decrease of the drug release [29,32].…”
Section: Influence Of the Dissolution Medium On The Release Of Dehydrmentioning
confidence: 99%
“…The nonionic surfactants in the suppository base incorporate some of the drug, which prevents its release [15]. There are many reports of studies on the effect of the addition of various types of surfactants on the drug release from the suppositories with lipophilic or hydrophilic bases [12,14,15,30]. The mechanism of action of surfactants is not completely known.…”
Section: Influence Of the Dissolution Medium On The Release Of Dehydrmentioning
confidence: 99%
“…The aim of present study is to prepare suppositories containing the fixed dose combination (FDC) of stavudine, lamivudine and nevirapine (SLN) for pediatric use. There were no suppository formulations for fixed dose combination of HIV drugs [9][10][11][12][13][14][15][16][17]. The suppository formulations in these studies were prepared from semi synthetic fatty bases.…”
Section: Introductionmentioning
confidence: 99%